Mechanical behavior enhancement of AZ31/WS2 and AZ61/WS2 magnesium metal matrix nanocomposites. (February 2018) - Huang, Song-Jeng; Lin, Chien-Cheng; Huang, Jheng-Yang; Tenne, Reshef
This study conducted tensile and hardness tests to compare the mechanical properties of Mg alloys and metal matrix composites with and without WS2 or multi-walled carbon nanotubes. We also examined the microscopic structures to investigate their failure characteristics. Our results indicate that AZ61 presented the best mechanical properties following the addition of WS2 and solution heat treatment, and increasing the content of WS2 improved the mechanical properties. This performance of this combination even outperformed that of metal matrix composites containing multi-walled carbon nanotubes. This study developed an image processing method, in which X-ray images of the metal matrix composite specimens undergo filtering, binarization, edge enhancement, and morphological calculations to determine the area of internal defects in Mg metal matrix composites. The results indicated reduced percentage of internal defect area values in AZ31-T4 and AZ61-T4 following the addition of 0.2% WS2 inorganic nanotube (INT). X-ray diffraction results revealed that the solution heat treatment process causes the WS2 to dissolve into the Mg base, thereby shifting the peak to the right. This improves solid solution strengthening and enhances the mechanical properties. Further observation of the microscopic structures indicated that the AZ61-T4 possesses finer grains than does the AZ31-T4, which is consistent with the existing literature.